PENINGKATAN PEMAHAMAN SISWA TENTANG OPERASI HITUNG DAN BILANGAN DALAM PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN METODE DISKUSI - Iin Sunarsih (Jurnal Pendidikan Dasar, 2019)
This research is motivated by the low understanding of students regarding arithmetic and numerical operations. This study aims to improve students' understanding of arithmetic and numerical operations in mathematics learning of students in the class I Cibentar III State Elementary School using the discussion method. The research method used by researchers is a classroom action research, with a total of 17 students. This research took place in 2 cycles, each cycle consisting of 2 actions. The techniques used in data collection are observation, tests, interviews, documentation, and field notes. The results showed that the application of the discussion method could improve students' understanding of arithmetic and numerical operations in learning mathematics in class I Cibentar III Elementary School.